Survey on Intra-specific Crossing and F1 Seedling Cultivation in Seven Combinations of Chinese Cherry - Liu, Zhen-Shan; Wang, Xiao-Rong; Chen, Qing; Wang, Hao; Zhang, Yong; Tang, Hao-Ru; Zhang, Yun-Ting; Luo, Ya; Zhang, Jing; Lin, Yuan-Xiu; Yang, Shao-Feng; Li, Meng-Yao; et al. (Horticulture journal, 2022)
The Chinese cherry (Prunus pseudocerasus/Cerasus pseudocerasus), which is native to China, is an economically important tetraploid fruiting cherry species. Its industry has been greatly limited due to some general disadvantages in the fruits such as small fruit size, high acid content, and short shelf-life. As such, it is urgent to carry out cross breeding and genetic improvement of this species. Here, seven cross combinations were designed by selecting five genotype landraces of the Chinese cherry and one semi-wild resource as cross parents. The fruit-set percentage, germination rate of the hybrid seeds, and growth status of the F1 seedlings varied among different parental genotypes and cross combinations. Three or four S-genotypes were detected in six tetraploid parents, with a maximum of five different alleles between two parents. Both the pollen vigor of the male parent and the differential S-genotype between parents may contribute to the variation in fruit-set percentages, ranging from 0 to 28.55%. Significant differences in the F0 fruit traits were observed among different combinations, indicating potential metaxenia of the Chinese cherry. Appropriate pretreatments, including the removal of endocarps, soaking with 150 mg/L GA3 for 24 h, and chilling stratification for 7–10 days, could significantly increase the germination rate of the hybrid seeds. According to the overall performance, using (semi)-wild resources as one of the parents should be taken into consideration more in Chinese cherry breeding programs. On the basis of these findings, we further constructed a flow chart for successful intra-specific crossing and efficient cultivation of robust F1 seedlings. This study will provide important references for the selection of cross parents, establishment of a feasible breeding program, and cultivation of robust F1 progenies of the Chinese cherry.